Business as service? Human Relations and the British interwar management movement. (August 2022) - Maclean, Mairi; Shaw, Gareth; Harvey, Charles
To what extent should business have an implication of service when its fundamental purpose is profit-seeking? We explore this issue through a contextually informed reappraisal of British interwar management thinking (1918–1939), drawing on rich archival material concerning the Rowntree business lectures and management research groups. Whereas existing literature is framed around scientific management versus human relations schools, we find a third pronounced, related theme: business as service . Our main contribution is to identify the origins in Britain of the discourse of corporate social responsibility in the guise of business as service. We show that this emerged earlier than commonly assumed and was imbued with an instrumental intent from its inception as a form of management control. This was a discourse emanating not from management theorists but from management practitioners, striving to put the corporate system on a sustainable footing while safeguarding the power, authority, and legitimacy of incumbent managerial elites.